PENGARUH EKSTRAK PEGAGAN (CENTELLA ASIATICA) DALAM MENINGKATKAN KAPASITAS FAGOSIT MAKROFAG PERITONEUM MENCIT TERHADAP SALMONELLA TYPHI - Besung, I Nengah Kerta (Buletin Veteriner Udayana; Vol. 3 No.2 Agustus 2011)
main problem in controlling and handling the disease is that only few antibiotics areavailable to cure the disease. In addition, the prolonged use of such antibiotics often leadsto a bacterial resistant against the antibiotics. Herbal drugs such as Centella asiatica (inIndonesia is known as pegagan) contains triterphenoids saphonin which acts asimmunostimulant capable of enhancing the phagocytic activity of macrophages. However,no study has been conducted to investigate the use pegagan in capacity of macrophage ofmice infected with Salmonella typhi. A study was therefore conducted to find out the abilityof Centella asiatica in enhancing phagocytic capacity of macrophages toSalmonella typhi.Experimental laboratory studies were conducted using Completely Randomized Design.Mice were divided into 4 groups and they were treated respectively with destilated water(negative control), 125, 250, dan 500 mg/kg bw of Centella asiaticaextract. The treatmentwas conducted daily for 2 weeks and the mice were then inoculated with 105 cells/ml of S.typhi. The capacity of macrophages were examined 24 hours following inoculation with S.typhi. The result showed that treatment of mice withCentella asiatica extract significantly(p<0,05) enhanced capacity of macrophages in phagocyting S. thypi. The highest capacityof macrophages were observed in mice treated Centella asiatica extract at the dose of 500mg/kg bw with the capacity of 209,12±26,17 cells per 50 macrophage.
Keywords: pegagan, C. asiatica, phagocytic capacity of macrophages